Using Project-Based Tasks in Mother Tongue Classes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article covers information about project-based education and project tasks, the stages of project implementation, views on the proper organization of educational and project activities. The importance of using project-based tasks in teaching the mother tongue is revealed. There are also examples of project tasks intended for use in mother tongue classes.